STUNTING RELATIONSHIP WITH DEVELOPMENT OF CHILDREN AGE 12-36 MONTHS IN THE REGION OF THE SAMBONG BLORA PUSKESMAS KEJA - Sifak Refin Pangesti; Rizky Amelia; Dhita Aulia Octaviani (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Province of Central Java is one of the provinces with a 32% high stunting rate. For the Blora Regency itself, is included in the top 10 highest stunting priority districts category. government implemented some efforts to controls that have been done, such as : prevention like raskin and PMT, scouting the grows of the toddlers in the clinic, giving zinc syroup to the stunting baby.This research aims to know the relationship between stunting and the 12-36 months old toddlers, in the working space of the Sambong's clinic, Blora Regency. The methode of this research is observation with crossection design. For the sampling, using Slovin formula with the cluster sampling with a total 56 respondents. The Instrument that was used is KPSP according to the aged of the toddlers. Analysis that was used is Kendall's Tau.The result shows that there is a relationship between stunting and the 12-36 months old toddlers, with the statisctic results using Kendall's Tau was obtained the value of p = 0,003 or 0,005.Total 56 stunted toddlers wirth short and very short classifications appropiate development were only 28,6%, dubious development are 60,7%, and development deviates are 10,7%. The mother of the toddlers is expected to be fulfill the nutrition of their toddlers and check-up routine to the health facilities for checking the growth and development of the toddlers so that can be scouted as well.